Traditional Chinese Medicine and Natural Products: Potential Approaches for Inflammatory Bowel Disease - Yuan, Shuo; Li, You; Li, Jiao; Xue, Jia-Chen; Wang, Qi; Hou, Xiao-Ting; Meng, Huan; Nan, Ji-Xing; Zhang, Qing-Gao (Frontiers in Pharmacology, 2022)
Inflammatory bowel disease (IBD) is a chronic, recurrent and intractable inflammatory disease of the gastrointestinal tract, usually accompanied by inflammatory cell infiltration and damage to the intestinal mucosa and carries a particular risk of cancer. The clinical use of drugs in western countries affects IBD treatment, but various adverse effects and high prices limit their application. For these reasons, Traditional Chinese Medicine (TCM) is more advantageous in treating IBD. This paper reviews the mechanism and research status of TCM and natural products in IBD treatment by analyzing the relevant literature to provide a scientific and theoretical basis for IBD treatment.